New Constraints on the Physical and Biological Controls on the Silicon Isotopic Composition of the Arctic Ocean - Brzezinski, Mark A.; Closset, Ivia; Jones, Janice L.; de Souza, Gregory F.; Maden, Colin (Frontiers in Marine Science, 2021)
The silicon isotope composition of silicic acid, δ30Si(OH)4, in the deep Arctic Ocean is anomalously heavy compared to all other deep ocean basins. δ30Si(OH)4 was examined on US GEOTRACES section GN01 from the Bering Strait to the North Pole to evaluate mechanisms controlling the Si isotopic composition of the Arctic and waters exchanged with adjacent oceans. The maximum in silicic acid concentration, [Si(OH)4],within the double halocline of the Canada Basin formed a local minimum in δ30Si(OH)4 that extended across the Canada Basin reflecting the high-[Si(OH)4] Pacific source waters and benthic inputs of Si(OH)4 in the Chukchi Sea. Isotope values in the Polar Mixed Layer showed a strong influence of the Transpolar Drift. Drift waters contained relatively high [Si(OH)4] with heavy δ30Si(OH)4 consistent with the high silicate in riverine source waters and strong biological Si(OH)4 consumption on the Eurasian shelves. δ30Si(OH)4 became lighter with the increase in [Si(OH)4] in intermediate and deep waters; however, both Canada Basin Deep Water and Eurasian Basin Deep Water were heavier than deep waters from other ocean basins. A preliminary isotope budget incorporating all available Arctic δ30Si(OH)4 data confirms the importance of isotopically heavy inflows in creating the anomalous deep Arctic Si isotope signature, but also reveals a surprising similarity in the isotopic composition of the major inflows compared to outflows across the main gateways connecting the Arctic with the Pacific and the Atlantic. This similarity implies a major role of biological productivity and opal burial in removing light isotopes entering the Arctic Ocean from rivers.